2008
DOI: 10.1007/s00436-008-0879-6
|View full text |Cite
|
Sign up to set email alerts
|

The use of microfluorometric method for activity-guided isolation of antiplasmodial compound from plant extracts

Abstract: In vitro antiplasmodial activity of methanolic extracts of 16 medicinal plants was evaluated by fluorometric assay using PicoGreen. The IC50s, as determined by parasite DNA concentration, ranged from <11 to >200 and <13 to >200 μg/ml for Plasmodium falciparum 3D7 and K1, respectively; and the most active extracts were those from Anogeissus leiocarpus and Terminalia avicennoides (<11-≥14 μg/ml). Aqueous, butanolic, ethyl acetate, and methanolic fractions of these two extracts revealed butanolic fraction to have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0
1

Year Published

2009
2009
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(40 citation statements)
references
References 28 publications
1
38
0
1
Order By: Relevance
“…Chloroform and ethanol extracts of whole plant of Euphorbia hirta L (Euphorbiaceae) showed antiplasmodial activity (Tona et al 1999) while the lipophilic fraction and ethanol extract in another study lacked activity (Kohler et al 2002;Zirihi et al 2005). Terminalia catappa Linn (Combretaceae) and other species of the genus Terminalia were reported to possess antiplasmodial activity (Mustofa et al 2000;Okpekon et al 2004;Shuaibu et al 2008; Abiodun personal communication). Likewise, extract of leaves of Jatropha curcas showed antiplasmodial activity (Abiodun personal communication) while absence of activity was observed in another similar study (Kohler et al 2002;Kaou et al 2008).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Chloroform and ethanol extracts of whole plant of Euphorbia hirta L (Euphorbiaceae) showed antiplasmodial activity (Tona et al 1999) while the lipophilic fraction and ethanol extract in another study lacked activity (Kohler et al 2002;Zirihi et al 2005). Terminalia catappa Linn (Combretaceae) and other species of the genus Terminalia were reported to possess antiplasmodial activity (Mustofa et al 2000;Okpekon et al 2004;Shuaibu et al 2008; Abiodun personal communication). Likewise, extract of leaves of Jatropha curcas showed antiplasmodial activity (Abiodun personal communication) while absence of activity was observed in another similar study (Kohler et al 2002;Kaou et al 2008).…”
Section: Discussionmentioning
confidence: 93%
“…This result is comparable to published work (Smilkstein et al 2004;Corbett et al 2004;Bacon et al 2007). The utility of PicoGreen® as a systematic and efficient means of screening large numbers of crude extracts, and compounds isolated from plants had been published previously (Corbett et al 2004;Shuaibu et al 2008). Here, we compared the utility of PicoGreen® and SYBR green I with [ 3 H]-hypoxanthine incorporation assay for evaluation of antimalarial activities of 21 plant extracts.…”
Section: Discussionmentioning
confidence: 98%
“…These plants cited are very well-known species widely used in the African pharmacopeia and already evaluated against Plasmodium falciparum, and part of plants tested were roots from Z. zanthoxyloides (Kassim et al 2005) and S. latifolius (Abreu and Pereira 2001), stem bark from C. molle (Asres et al 2001), and A. leiocarpus (Shuaibu et al 2008). It is known that the use of these parts of plants for the treatment of an endemic disease like malaria is not suitable for plant preservation so that the present study aims to investigate the potential in vitro antiplasmodial activity of the other parts of these plants which were never been evaluated yet for antiplasmodial properties and for which the use even at large scale could preserve the survival of the plants and the ecology better than the parts currently used by scientists or traditional healers.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the activity of these two plants against P. falciparum NF54 was reported using three different in vitro techniques (Abiodun et al, 2010). Previous reports of in vitro antiplasmodial activity of other species of the genus Terminalia had been reported (Okpekon et al, 2004;Shuaibu et al, 2008). A previous study reported that extracts of leaves of Terminalia catappa were more cytotoxic to human hepatoma cells than to normal liver cells (Ko et al, 2003).…”
Section: Resultsmentioning
confidence: 99%
“…Flavonoid glycosides, squalene, ursolic acid, 2α, 3β, 23-trihydroxyurs-12-en-28-oic and hydrolysable tannins were isolated from the leaves of T. catappa (Fan et al, 2004;Chen & Li, 2006;Lin et al, 2001). Similarly, hydrolysable tannins such as ellagic acid, flavogallonic acid, punicalagin and terchebulin isolated from stem bark of Terminalia avicennoides showed in vitro antiplasmodial activity with no cytotoxic effect on a mammalian cell line (Shuaibu et al, 2008). Several flavonoids had been shown to exert antiplasmodial activity (Ahmed et al, 2001).…”
Section: Resultsmentioning
confidence: 99%